Comparison of the detection of Helicobacter pylori infection by commercially available serological testing kits and the 13C-urea breath test. Issue 10 (October 2019) - Kawai, Sayo; Arai, Kensuke; Lin, Yingsong; Nishiyama, Takeshi; Sasakabe, Tae; Wang, Chaochen; Miwa, Hiroto; Kikuchi, Shogo
Abstract: Background: Serum Helicobacter pylori ( H. pylori ) antibody kits (LZ and LIA) using the latex agglutination immunoassay method are commercially available, but few studies have been performed to determine their diagnostic accuracy or to compare their results with those of enzyme-linked immunosorbent assay (ELISA) kits (EP and EIA). Methods: Sera were obtained from 213 hospital outpatients with dyspeptic symptoms. The serological results were compared with the result of the 13 C-urea breath test (UBT) which seems to be reliable. Results: Of the 213 subjects, 154 were diagnosed as positive for H. pylori infection according to the UBT. The sensitivities and specificities of these tests were 97.4% and 76.3%, 98.1% and 78.0%, 99.4% and 74.6%, and 98.1% and 71.2% for the EP, LZ, EIA and LIA tests, respectively. When the 13 subjects whose seropositive results of the four kits were completely opposite to the negative results of the UBT were excluded, the specificities of evaluated kits were all higher than 90%. The concordance rate between the EP and EIA tests was 98.1% (Spearman's rank correlation coefficient = 0.83) and that between the LZ and LIA tests was 97.1% (correlation coefficient = 0.91). The LZ gave higher antibody titer value than EP ( p  < 0.0001, Z = 9.82; Wilcoxon signed-rank test), and EIA gave higher value than LIA ( p  < 0.0001, Z = 6.43; Wilcoxon signed-rank test). Conclusions: The latex immunoassay method provided the same reliability to ELISA in terms of the diagnostic accuracy for current H. pylori infection, although we should take into account the titer value differences by each test method in practical use.